ASSOCIATION OF IRON DEFICIENCY ANEMIA WITH ACUTE LOWER RESPIRATORY TRACT INFECTIONS IN CHILDREN - Nawaz, Raazia; Hussain, Shabbir; Khushdil, Arshad; Tanveer, Sidra; Javed, Maria; Akram, Saira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To establish association between acute lower respiratory tract infection and iron deficiency anemia.Study Design: Case-control study.Place and Duration of Study: Pediatrics Department, Pak Emirates Military Hospital, Rawalpindi, from Dec 2017 to May 2018.Methodology: A total of 100 children with age ranging from 6-60 months were selected for this study with 50 being in each group. Study group constituted of children presenting with acute lower respiratory tract infection and healthy children presenting to outpatient were taken as controls. Hemoglobin levels (